The Best Response Paradigm: A New Approach to Test Implicatures of Complex Sentences - Gotzner, Nicole; Benz, Anton (Frontiers in Communication, 2018)
There is a controversial debate about which implicatures are triggered by logically complex sentences. This paper introduces a novel experimental paradigm based on a game theoretic design to test these implicatures. In particular, we investigated two cases adjudicating between different accounts of implicature (‘Each girl found some of her marbles’ and ‘Some of the girls found some of their marbles’). The advantage of our paradigm is that we can provide an explicit game theoretical model of the experimental situation so that participants’ interpretation of test sentences can be read off from their choices between various actions (rather than requiring metalinguistic judgements). The study shows that, in our scenario, strong (embedded) implicatures are drawn reliably. We evaluate the predictions of several structural and game-theoretic accounts for the data and discuss the broader relevance of the findings for theories of implicature and the framework they belong to.